Superhydrophobic (PVDF) Membrane Incorporated With Silica Nanoparticles For Carbon Dioxide Absorption - Zainal, Mohammad Amirul Asyraf Maula (Universiti Sains Malaysia, 2017)
Carbon dioxide is believed to be the main gaseous contaminant in the atmosphere. Conventional gas processes such as gas absorption for CO2 capture suffer several limitations including high energy consumption, flooding, foaming, entraining, channeling, high capital and operating costs. Developing new methods and technologies that compete with conventional industrial process for CO2 capture is a hot topic in recent research. Membrane contactor for gas absorption is a promising replacement technology for removal of CO2 in order to mitigate the global warming issue. In this study, Superhydrophobic (PVDF) membrane incorporated with silica nanoparticles were proposed for CO2 absorption. Silica nanoparticles were used as fillers to improve CO2 gas flux. The asymmetric membrane structure was prepared using phase inversion method in order to enhance CO2 captured. The effects of Silica nanoparticles loading (0.5-1 wt%) on the membrane characteristic and treatment by modification with silane were studied. The most optimum sample is the membrane with 1 wt% of Silica nanoparticles loading, modified by silane which exhibit improved CO2 flux at the absorbent flow rate of 220 mL/min (0.031 m/s velocity). Relatively high CO2 flux (3.89 × 10−4 mol/m2s) was achieved for the P1.0F membrane, which was almost double the flux of the plain PVDF membrane. This also proved that the membrane that undergoes modification with silane will have higher CO2 flux, compared to other samples.